2022
DOI: 10.1097/brs.0000000000004529
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Scoliosis Lenke type 5, Anterior versus Posterior, which Approach is Better? A Systematic Review and Meta-analysis

Abstract: Study Design. Systematic review and meta-analysis.Objective. This study aimed to compare the radiographical and clinical outcomes between anterior spinal fusion (ASF) and posterior spinal fusion (PSF) in Lenke type 5 adolescence idiopathic scoliosis. Summary of Background Data. PSF has been the standard operation for adolescence idiopathic scoliosis. ASF can also achieve a good curve correction effect with fewer fusion segments and minor invasion of paraspinal structures. Materials and Methods. A systematic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…In this meta-analysis from Beijing (China) , the clinical and radiological outcomes of each strategy are analyzed in an attempt to establish which option currently appears to give superior results. 3 Overall, 12 studies met the inclusion criteria following an extensive and well-constructed systematic search. These studies reported a cohort of 819 patients, comprising of 427 patients treated through an anterior spinal fusion (ASF) and 392 treated through a posterior spinal fusion (PSF).…”
Section: Lenke Type 5 Anterior or Posterior: Systematic Review And Me...mentioning
confidence: 99%
“…In this meta-analysis from Beijing (China) , the clinical and radiological outcomes of each strategy are analyzed in an attempt to establish which option currently appears to give superior results. 3 Overall, 12 studies met the inclusion criteria following an extensive and well-constructed systematic search. These studies reported a cohort of 819 patients, comprising of 427 patients treated through an anterior spinal fusion (ASF) and 392 treated through a posterior spinal fusion (PSF).…”
Section: Lenke Type 5 Anterior or Posterior: Systematic Review And Me...mentioning
confidence: 99%
“…Patients with Lenke types 1-4 and type 6 AIS curves were also excluded. The average age and body height at operation were 14.7 ± 1.9 years (range, [12][13][14][15][16][17][18] and 157.7 ± 6.6 cm (range, 149-173), respectively.…”
Section: Patientsmentioning
confidence: 99%
“…Although the anterior approach remains useful for Lenke type 5 AIS, posterior spinal fusion with pedicle screw instrumentation is currently the standard technique, with a relatively low complication rate [8][9][10]. Some authors have demonstrated that the posterior approach has no significant difference in the coronal and sagittal correction compared to the anterior approach, although the anterior approach has the advantage of saving fusion levels [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%